Enhancing Students’ Concepts Mastery in Kinetic Theory of Gases Through the STEM-Discovery Learning Model - Susanti, Shinta Dewi; Yuliati, Lia; Purwaningsih, Endang; Putri, Febi Dwi (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
Students' difficulties with gas kinetic theory material have led to low mastery of physics concepts. Improving mastery of the concept of the kinetic theory of gases can be supported by using learning models. There have been many studies that prove that discovery learning can influence physics learning outcomes. However, this study uses a STEM approach integrated into a discovery learning model that acts as part of the inquiry level in physics classes Merdeka curriculum. This research aims to improve students' mastery of concepts in the kinetic theory of gases material through the STEM-discovery learning model. This research used a one-group pretest and posttest design on 30 students of class XI Merdeka 4 at SMAN 1 Dolopo. The instruments used are the RPP and five questions describing the concept mastery test. The data obtained was then analyzed using the normality test, difference test, N-gain, and effect size, and categorizing the students' concept mastery level for each question. The results of this research reveal that STEM-discovery learning is able to increase students' mastery of concepts in kinetic gas theory material. Interestingly, this research also found that students' correct conceptions have not been able to be stored in memory very well, so it is necessary to link kinetic gas theory material to other physics material that is still relevant so that students are motivated to remember and retain concepts.